1979
DOI: 10.1111/j.1600-0773.1979.tb02393.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Response to Ethanol in Relation to Acetaldehyde Levels and Dopamine‐β‐hydroxylase Activity in Rats Pretreated with Disulfiram, Cyanamide and Coprine

Abstract: The blood pressure response after ethanol administration was studied in relation to blood acetaldehyde levels, aldehyde-dehydrogenase (ALDH)and dopamine-P-hydroxylase (DBH) activities in rats pretreated with the ethanol-sensitizing compounds disulfiram, cyanamide and coprine and the DBH-inhibitor FLA-57. Disulfiram, cyanamide and coprine, but not FLA-57, inhibited the low-K, ALDH in the liver and caused an increased acetaldehyde level in blood. Disulfiram and FLA-57, but not cyanamide and coprine, decreased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The esterase activity of ALDH is also inhibited, albeit to a lesser extent compared with the dehydrogenase activity (Marchner and Tottmar, 1983). Unlike disulfiram (see below), it does not inhibit dopamine ␤-hydroxylase (Carlsson et al, 1978;Tottmar and Hellstrom, 1979). Despite its potency at inhibiting ALDH activity, mutagenic and gonadotoxic side effects prevented further pursuit of this compound as a candidate for drug development (Michelot, 1992).…”
Section: F Coprinementioning
confidence: 99%
See 1 more Smart Citation
“…The esterase activity of ALDH is also inhibited, albeit to a lesser extent compared with the dehydrogenase activity (Marchner and Tottmar, 1983). Unlike disulfiram (see below), it does not inhibit dopamine ␤-hydroxylase (Carlsson et al, 1978;Tottmar and Hellstrom, 1979). Despite its potency at inhibiting ALDH activity, mutagenic and gonadotoxic side effects prevented further pursuit of this compound as a candidate for drug development (Michelot, 1992).…”
Section: F Coprinementioning
confidence: 99%
“…Consumption of alcohol by patients given therapeutic doses of disulfiram results in acetaldehyde accumulation, the physiological consequences of which include low blood pressure, tachycardia, facial flushing, nausea, and vertigo (Bell and Smith, 1949). These symptoms, collectively called disulfiram ethanol reaction (Tottmar and Hellstrom, 1979;Marcato et al, 2011), serve as the means by which the individual is discouraged from indulging in alcohol intake. Disulfiram itself inhibits ALDH1A1 more potently that it does ALDH2 (Moore et al, 1998), which led to some early confusion as to the identity of the enzyme inhibited in vivo.…”
Section: J Disulfirammentioning
confidence: 99%
“…Throughout the years, differences have been verified between the amines used as hemodynamic support, with norepinephrine proven to be more efficient than dopamine. This is thought to be due to the effects of diethyldithiocarbamate, one of disulfiram's metabolite, which attenuates the effect of the adrenergic response to hypotension by inhibiting dopamine beta-hydroxilase, the enzyme that converts dopamine into norepinephrine 6,8 . Norepinephrine depletion at the heart and vessels permits direct action of acetaldehyde in these tissues, thus producing the typical cardiovascular symptoms, including severe hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Acetaldehyde is a toxic metabolite of ethanol that causes the classical symptoms of headache, nausea, palpitation and facial flushing [2,4]. Elevation of acetaldehyde has also been shown to alter blood pressure in experimental animal models [5-7]. In addition to alcohol-metabolizing activity, recent research has identified ALDH2 as an enzyme responsible for the bioactivation of nitroglycerin in animals and human.…”
Section: Introductionmentioning
confidence: 99%